Souvenir and Abstracts from PANCON Dharan 2019 - Shakya, Dhana Ratna; Sapkota, Nidesh; Nepal, Suraj; Kunwar, Mandeep; Thapa, Arati (Journal of Psychiatrists' Association of Nepal, 2019)
Abstracts from PANCON Dharan 2019 7th National Conference of Psychiatrists' Association of Nepal. Theme: 'Many faces of Psychiatry in the Changing World'. Held at B.P. Koirala Instutute of Health Sciences, Dharan, Nepal March 7-8 2019 (Falgun 23-24, 2075 BS)